Comment moderation strategies in Canadian news media and their principles - Al-Rawi, Ahmed; Nicolai, Joseph (ALBAHITH ALALAMI, 2022)
This paper offers a critical examination of Canadian news guidelines and policieson user-generated content (UGC) posted on news-related comment sections andsocial media.The outline of how news-related UGC is moderated within Canadian news is achievedby looking at the online comment policies of major Canadian news organizations like .the CBC, CityNews (Halifax), CTV News, Glacier Media, Global News, The Globeand Mail, Narcity Media, Postmedia, QUB (Québecor), and Torstar.The policies highlight how Canadian news organizations have practical strategiesto manage news-related UGC but also call upon positive and negative socialprinciples, to flag ill practices, foster democracy, and fight against online hate speechand libel. The analysis shows how guidelines reflect many of the key principles highlightedin the literature review but make no reference to economic principles thatare emphasized as important in academic and journalist concerns with moderatingnews-related UGC.